Recent advances in BazookaSPECT: Real-time data processing and the development of a gamma-ray microscope - Miller, Brian W. (2008)
Recent advances have been made with the BazookaSPECT detector, a high-resolution CCD-based gamma camera which utilizes an MCP-based image intensifier for upfront optical gain. Operating the gamma camera at high frame rates leads to a massive amount of data throughput, thereby inducing the need for real-time processing. We have developed and implemented a list-mode algorithm which allows for real-time data acquisition and processing at high frame rates. This is accomplished with a graphics processing unit (GPU), which provides processing capabilities in addition to the CPU. We have also developed a gamma-ray microscope based on the BazookaSPECT detector and micro-coded apertures. Experimental phantom images show the gamma-ray microscope having an estimated reconstruction resolution of ~30 μm, an unprecedented resolution in gamma-ray imaging.